Disease resistance of improved MR220 lines against Pyricularia oryzae Cavara and their preliminary agronomic performance - Mohamad, Siti Nor Aziemah; Ab. Ghaffar, Mohamad Bahagia; Othman, Ahmad Sofiman; Misman, Siti Norsuha; Abd Rahman, Zuraida; Ab Razak, Mohd Shahril Firdaus; Ahmad Seman, Zulkifli; Mohd Yusof, Muhammad Fairuz; Ahmad, Khairulmazmi; Hashim, Habibuddin (Czech Academic of Agricultural Science, 2021)
Blast disease caused by Pyricularia oryzae is one of the most destructive fungal diseases of rice in Malaysia. Utilisation of resistant varieties is the most efficient management approach towards reducing yield losses. The line IRTP21683 with the Pi9 gene has shown strong resistance against the isolate MPO988.3 of pathotype P0.0, the most prevalent P. oryzae pathotype in Malaysia. Crossing of IRTP21683 was undertaken with the recurrent parent MR220, a susceptible elite Malaysian rice variety, using a marker assisted backcrossing technique with two simple sequence repeat markers, RM19776 and RM7311, as the tag for the Pi9 gene. Twenty BC3F4 lines with the Pi9 gene were resistant when challenged with MPO 988.3. The cluster analysis based on seven agronomic parameters showed that the resistant BC3F4 lines could be divided into four groups, of which the members in group 1 and 2 have shown comparable or better performance than MR220. Five lines in group 1, B220PI9-3-48, B220PI9-3-76, B220PI9-3-77, B220PI9-3-79 and B220PI9-3-82 showed outstanding yield performance with early maturation.